The Correlation between Students’ Learning Styles and Their Academic Achievement at English Education Department of Universitas Muhammadiyah Yogyakarta - Rizka Puspitasari (PBI 15 UMY 035, 2015)
*35 Learning styles are one of the important factors which eventually may result in a good academic achievement. The purpose of this study is to find out the correlation between students’ learning styles (visual, auditory, kinesthetic or V-A-K) and their academic achievement at English Education Department (EED) of Universitas Muhmmadiyah Yogyakarta (UMY). In this study, there were two variables, namely the independent variables (X) that consist of three variables (visual – auditory – kinesthetic or V-A-K) and the dependent variable (Y). The problem was formulated into five research questions to be examined in this study. The study was designed as quantitative study. The setting of this research was in English Education Department, Faculty of Language Education of UMY. The sample that was used in this research was convenience sampling with the respondents were 75 students of Batch 2012 at English Education Department of UMY. To collect the data, the researcher distributed the questionnaire namely Perceptual Learning Styles Preference Questionnaire (PLSPQ) to the respondents. Meanwhile, Pearson’s Product Moment correlation was used to analyze the correlation. Also, the document of students’ academic achievement or Grade Point Average (GPA) was obtained to support this research. The findings showed that students’ highest learning style was kinesthetic (45.33%), followed by auditory (28.00%) and then visual (26.67%). The correlation between the students’ learning styles and their academic achievement, the positive significantly correlation appeared from the students’ kinesthetic viii learning style (r = 0.235 and sig. 0.042). Meanwhile, for both students’ visual and auditory learning styles had no positive correlation or it were negative correlation. Finally, it can be concluded that students’ learning styles probably do not always influence their academic achievement (GPA). However, the students who actively engaged in the teaching and learning process were the students with kinesthetic learning style.